Efek Kompetitif Merger Bank Syariah Indonesia Terhadap Penyaluran Pembiayaan UMKM Dan Non-UMKM - Fadilla , Anisa (WADIAH, 2024)
Bank Syariah Indonesia (BSI) is merged of three state-owned subsidiary Islamic banks, namely Bank Syariah Mandiri (BSM), Bank Negara Indonesia (BNI) Syariah, and Bank Rakyat Indonesia Syariah (BRIS). The merger of the three banks is expected to provide benefits, especially for the majority of Indonesian Muslims. In addition, it can also increase the value of the company by increasing profits both through raising funds and distributing financing. This study was conducted to examine the competitive effect of Bank Syariah Indonesia merger on the distribution of UMKM financing, non-UMKM financing, total financing. The bank's performance to be tested consists of market share, net trade cycle (NTC), investment, interest expense, and return on asset (ROA) in pre and post merger at Bank Syariah Indonesia. This study used 53 data, 5 bank data after the merger and 48 bank data before the merger to test the hypothesis whether there is an influence of market share, NTC, investment, ROA on UMKM financing, non-UMKM financing and total financing. The results showed that investment variables affect UMKM financing, non-UMKM financing and total financing while market share, NTC, interest expense, and ROA variables do not affect UMKM financing, non-UMKM financing and total financing.